Status GAKY, anemia, EYU, dan kesegaran jasmani anak sekolah dasar di Kabupaten Dairi, Sumatra Utara - Joner Lumban Toruan; Wara Kushartanti; Untung Widodo (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2009)
Background: Iodine deficiency disorder (IDD) and anemia are major health problems in Indonesia. Prevalence of TGR according to the result of IDD survey 2003 in District of Dairi is 33,9%. Prevalence of anemia according to Household Health Survey 2001 is 47% for children of 0–5 years old; 26.5% for school children; and 40% for eligible women. The result of a survey in Jakarta capital city special territory 2004 shows that prevalence of anemia is 26.5% for children under five and 43.5% for pregnant mothers. Thyroid hormone regulates metabolism and plays an important role in calorie production, whereas haemoglobin in the blood may distort metabolism of energy in the muscles leading to fatique.Objective: The objective of the study was to identify the relationship between IDD, anemia, and physical fitness and to assess differences in physical fitness according to endemic level.Method: The study was observational with cross sectional design. Location of the study was District of Dairi, Sumatra Utara. Palpation was used to identify endemic level. Three elementary schools were chosen according to endemic level. Number of samples per district and elementary school was determined using quota, and samples were selected from grade 4–6 using systematic random sampling technique. Data analysis used univariable, bivariable, and multivariable techniques. Chi square (χ2) was used to identify the relationship between independent variable and dependent variable, 2 and ANOVA test (F test) was used to find out differences in physical fitness based on endemic level.Results: The result of statistical test showed that the relationship between IDD and physical fitness was p = 0.675 with OR 0.8 (95% CI: 0.499–1.498). The relationship between anemia and physical fitness was p = 0.003 with OR 2.29 (95% CI: 1.33–3.95). There were differences in physical fitness according to endemic level with p < 0.001.Conclusion: There was no relationship between IDD and physical fitness, but there was relationship between anemia and physical fitness and there was difference in physical fitness according to endemic level.